Let's drink to your health! a self-help guide to sensible drinking - Heather, Nick; Robertson, Ian 1951- (The British Psychological Society, 1996)
This is a revised & updated ed. of the self-help guide by Nick Heather & Ian Robertson. It takes into account feedback received from many alcohol & counselling agencies, and is for those of us who think that we are drinking more than we should.
Keywords: Alcoholism -- Treatment